Current state and future perspectives of the Latin American Society for Immunodeficiencies (LASID) (2015)
ABSTRACT: Primary immunodeficiencies (PID) are genetic diseases that affect the immune system and for the last 20 years, the Latin American Society for Immunodeficiencies (LASID) has been promoting initiatives in awareness, research, diagnosis, and treatment for the affected patients in Latin America. These initiatives have resulted in the development of programmes such as the LASID Registry (with 4900 patients registered as of January 2014), fellowships in basic and clinical research, PID summer schools, biannual meetings, and scientific reports, amongst others. These achievements highlight the critical role that LASID plays as a scientific organisation in promoting science, research and education in this field in Latin America. However, challenges remain in some of these areas and the Society must envision additional strategies to tackle them for the benefit of the patients. In June 2013, a group of experts in the field met to discuss the contributions of LASID to the initiatives of PID in Latin America, and this article summarises the current state and future perspectives of this society and its role in the advance of PIDs in Latin America.